Re-visiting transition-based teaching: Impact of pre-service teacher's implementation on child outcomes. (February 2019) - Rakap, Salih
Abstract: Present study investigated impact of pre-service teachers' implementation of a constant time delay procedure within the framework of transition-based teaching on teaching pre-academic skills to three preschool children with developmental delays during transitions in inclusive classrooms. A multiple probe design across behaviors replicated across three children was used. Results indicated pre-service teachers could implement transition-based teaching with very high fidelity following a brief training session; pre-service teachers' implementation of transition-based teaching resulted in acquisition of pre-academic skills by all three participating children with developmental delays; children generalized the pre-academic skills they learned to other teachers, settings, and materials; and they maintained high levels of correct responding during the follow-up sessions. Moreover, pre-service and preschool teachers found transition-based teaching acceptable and effective. Directions for future research and practice are discussed. Highlights: Children spend large proportion of school day in transitions between activities and locations. Embedding instruction within transitions is a viable way of teaching pre-academic skills to young children with disabilities. Brief trials delivered during transitions do not increase length of transition times or change nature of teachers' behaviors. Teachers can learn and implement the transition-based teaching with high fidelity following a brief training session. Children learning skills through transition-based teaching are able to generalize and maintain the learned skills.